Abordagem ergonômica da atividade: a compreensão de determinantes do trabalho dos coletores de resíduos sólidos urbanos - Oliveira, Talita Martins (2020)
This research used as object of study the work of solid urban waste collectors, in which it requires great effort from this individual to complete his task, which is to handle household waste, in addition to moving around in an environment full of variability. The aim of this study was to analyze the determinants of the garbage collectors' work, showing physical, cognitive and organizational components. A case study was carried out, guided by the perspective of Activity Ergonomics in which data collection took place through systemic and unsystematic observations with the aid of filming, with tests to understand the physiological variables, the physical and mental load involved. during the execution of the task. After the field follow-up, the task description form was carried out, an interview with 50 collectors, 5 managers and 50 residents. The results obtained explained the dynamics involved in the organization of work, the task performed by the collector and real activity, elucidating its intrinsic and extrinsic variability, physical load accompanied by the results obtained through field data and controlled tests as well as the mental workload and operating modes. It is concluded that, in the collector's work routine, it is possible that the physical and mental fatigue is related to the overload arising from the work systems that still need to be modernized, thus allowing operations performed by the collector to enable greater regulation, expanding the margin maneuver. Understanding how the collector turns the prescription of the activity into real work has made it possible to discover that the public cleaning system has been moving slowly for a long time. In this context, it’s up to the worker, who is at the end of the production chain, to be responsible for adjusting to meet the objectives of the job, with some tools, some technology and much of their know-how to transform the task into real work.